1999
DOI: 10.1074/jbc.274.21.14678
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of a Novel Zinc Finger Transcriptional Repressor

Abstract: We have identified a novel transcriptional repressor, AEBP2, that binds to a regulatory sequence (termed AE-1) located in the proximal promoter region of the aP2 gene that encodes the adipose fatty acid-binding protein. Sequence analysis of AEBP2 cDNA revealed that it encodes a protein containing three Gli-Krü ppel (Cys 2 -His 2 )-type zinc fingers. Northern blot analysis revealed two transcripts (4.5 and 3.5 kilobases) which were ubiquitously expressed in every mouse tissue examined. In co-transfection assays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 33 publications
5
46
0
Order By: Relevance
“…[18][19][20][21][22][23][24][25][26]55,56 The KRAB-domain represses the activity of CMV-promoter through direct communications with TATA box-dependent basal transcription machinery, 18,55 whereas mSIN3B interacts with essential DNAbinding proteins that place it in a promoter context in which it can repress transcription by recruiting proteins that condense chromatin by histone deacetylation. 19 In contrast to KRAB-A or mSIN3B, the Zik1-repressor domain does not repress gene transcription from the CMV gal -promoter and some of the other repressor domains showed only weak repression of CMV galactivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20][21][22][23][24][25][26]55,56 The KRAB-domain represses the activity of CMV-promoter through direct communications with TATA box-dependent basal transcription machinery, 18,55 whereas mSIN3B interacts with essential DNAbinding proteins that place it in a promoter context in which it can repress transcription by recruiting proteins that condense chromatin by histone deacetylation. 19 In contrast to KRAB-A or mSIN3B, the Zik1-repressor domain does not repress gene transcription from the CMV gal -promoter and some of the other repressor domains showed only weak repression of CMV galactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Expression vectors for repressor fusion proteins of GAL4-DBD were kindly provided by: L Lania, Neaples, Italy (KRAB-A), 18 RA DePinho Boston, USA (m-SIN3B-SF and m-SIN3B-LF), 19 DJ Hall, Philadelphia, PA, USA (ZF87/MAZ), 20 K Bomsztyk, Seattle, USA (ZIK1), 21 LM Staudt, Bethesda, MD, USA (BCL-6), 22 C Bartholomew, Glasgow, Scotland (EVI-1), 23 Y Shi, Boston, USA (YY), 24 H-S Ro, Halifax Canada (AEBP2) 25 and A Bird, Edinburgh, UK (MeCP2 170-310 and MeCP2 209-492). 26 …”
Section: Cell Lines and Plasmidsmentioning
confidence: 99%
“…ZFDs have been implicated in many functions, including DNA recognition, protein/protein interactions, transcriptional repression, and nuclear localization (52)(53)(54)(55)(56). Examination of the secondary structure of the Glis1 zinc finger domain indicated that the second half of each zinc finger consists of an ␣-helix.…”
Section: Discussionmentioning
confidence: 99%
“…The C 2 H 2 zinc fingers of Jing are most similar (50% identical) to those of the mouse adipocyte enhancer binding protein 2 (AEBP2) and also show 25% homology to those of the Krü ppel family of transcription factors, including those encoding gli and ZIC2 (Liu and Montell 2001). AEBP2 function is implicated in chromatin remodeling events (Cardoso et al 1998;Cao and Zhang 2004) and has strong expression in the brain (He et al 1999).…”
Section: Discussionmentioning
confidence: 99%